Effect of Growth and Development on the Qualitative Attributesof Lasiurus Sindicus Henr - Gupta, Ashok K (Annals of Arid Zone, 2016)
Variations in the qualitative attributes of Lasiurus sindicus Henr. with the plant growth were studied. Cell wall constituents viz. NDF ADF, lignin, cellulose, hemicellulose and silica content increased significantly with plant growth while crude protein and in vitro dry matter digestibility decreased significantly in all the three years of study. NDF, ADF, lignin and cellulose were positively and significantly inter-correlated. However, they showed negative correlation with protein content and digestibility. Fodder quality, in terms of digestibility, was best correlated with crude protein and its prediction value was maximum (Ra = 0.9322) with crude protein as a single factor.